Human reproductive biology - Mader, Sylvia S. (McGraw-Hill, 2005)
Human Reproductive Biology, 3rd edition emphasizes the biological and biomedical aspects of human reproduction, explains advances in reproductive science and discusses the choices and concerns of today. Generously illustrated in full color, the text provides current information about human reproductive anatomy and physiology. The ideal book for courses on human reproductive biology - includes chapter introductions, sidebars on related topics of interest, chapter summaries and suggestions for further reading. * All material competely updated with the latest research results, methods, and topics now organized to facilitate logical presentation of topics * New chapters on Reproductive Senescence, Conception: Gamete Transport, Fertilization, Pregnancy: Maternal Aspects and Pregnancy: Fetal Development * Full color illustrations, New companion website featuring latest information on current related topics